CARIES OVERVIEW IN PRIMARY SCHOOL STUDENTS ASSISTED BY DENTAL SCHOOL PROGRAM CIMAHI PUBLIC HEALTH CENTRE (GAMBARAN PENYAKIT KARIES MURID SEKOLAH DASAR BINAAN USAHA KESEHATAN GIGI SEKOLAH PUSKESMAS DI KOTA CIMAHI) - Badi Soerachman; Syarif Soewondo; Syifa Khairunnisa Mauluddin (Fakultas Kedokteran Gigi Unjani, 2022)
Public Health Centre/Pusat Kesehatan Masyarakat (Puskesmas) in Indonesia planned dental and oral health efforts aimed at specific groups continuously in the promotive, preventive, and curative fields is through the Dental School Program/Usaha Kesehatan Gigi Sekolah (UKGS) program. UKGS is divided into three stages consisting of UKGS stage 1 (minimal package), stage 2 (standard package), and stage 3 (optimal package). This study aimed to examine the three stages of UKGS held by the Public Health Centre in the case of caries disease that occurs in primary school students in Cimahi. This research was a descriptive study by conducting the DMFT index in 12-year-old primary school students. Primary school selection was taken by random cluster sampling, and the number of participants was 87 students. The number of samples needed for this study used the determination of total sampling. It was obtained in UKGS primary school stages 1 (41 students), stage 2 (33 students), and stage 3 (13 students), and subjects were taken based on inclusion and exclusion criteria. The study results show that the DMFT index for primary school students assisted by UKGS stage 1 at the level of 5,14, UKGS stage 2 at the level of 3,06, and UKGS stage 3 at the level of 1,23. There are also DMFT score levels between male and female students; scores of 3,5 (male) and 2,6 (female). DOI : 10.54052/jhds.v1n3.p299-308